Researching the culture in agri-culture: social research for international development - Cernea, M. M.; Cernea, M. M.; Kassam, A. H.; Kassam, A. H. (Wallingford :CABI Publishing, 2005)
This book analyses the functions, content, methods, findings and impact of social and cultural research carried out by the worldwide network of 16 international agricultural research centres of the CGIAR. It brings together the perspectives of 50 eminent scholars and social researchers from 30 countries working within the centres or in outside academic and development institutions. The contributions examine critically the priorities, strengths, and weaknesses of research on the sociostructural, behavioural, cultural and institutional variables of developing agriculture, forestry, livestock and fisheries. The studies focus on farmers' values, needs, knowledge, their patterns of social organization, issues of food security, natural resource management and poverty reduction. Alternative models of multidisciplinary research, reuniting biological, natural, economic and social sciences, are scrutinized in the light of experience and results, with emphasis on the nature of social science research as a source of international public goods and a key contributor to induced development. The book is intended for researchers of agricultural and rural development, economics, sociology, culture and anthropology. It has 22 chapters in addition to an editors' preface, and has a subject index.
Keywords: AA000 - Agriculture (General); AA500 - Research; EE110 - Agricultural Economics; EE116 - Food Economics, (New March 2000); EE950 - Income and Poverty; KK000 - Forestry, Forest Products and Agroforestry (General); MM110 - Fisheries; PP000 - Natural Resources (General); UU485 - Social Psychology and Social Anthropology, (New March 2000); UU850 - Rural Development, (New March 2000)